Ruptured amoebic liver abscess with empyema thoracis - a case report - C., Danny Darlington; Anitha G., Fatima Shirly (International Surgery Journal, 2017)
Amoebiasis is one of the leading causes of deaths in the world. Though the most common manifestation is colitis, liver and lung involvement can occur. High index of suspicion is warranted to diagnose this condition. Apart from surgery and drainage, medical treatment is also important. We present a five year old boy with ruptured amoebic liver abscess with right empyema thoracis and right sided psoas abscess. The boy recovered well after timely percutaneous drainage and antibiotics. This case highlights the importance of serology and imaging in the diagnosis of this rare manifestation of a common etiology.